(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This study evaluated the effect of monitoring, that is, the presence or absence of different social agents (adult and child), in children’s self-report accuracy on their own performance in a reading task. Six children aged between nine and 10 years old participated. “Doing” consisted of reading aloud a word presented on a computer screen and “saying” consisted of reporting, after hearing an automated computer feedback, whether the reading was correct or not. Experimental conditions were implemented without monitoring, that is, in the absence of social agents (A), and with monitoring, that is, in the presence of an adult (B) or a child (C), in a reversal design (ABACA and ACABA). The results showed that monitoring produced an increase in the correspondence levels of error reports for all participants and there was no difference in the correspondence patterns depending on the type of monitor.